The first case of meningitis associated with SARS-CoV-2 BA.2 variant infection with persistent viremia. (November 2022) - D'Abramo, Alessandra; Vita, Serena; Colavita, Francesca; Cimini, Eleonora; Haggiag, Shalom; Maffongelli, Gaetano; Valli, Maria Beatrice; Bevilacqua, Nazario; Corpolongo, Angela; Giancola, Maria Letizia; Maggi, Fabrizio; Agrati, Chiara; et al.
Highlights: Neurological disorders during COVID-19 are rare. Plasmatic viremia could be persistent in patients who are immunocompromised. Immunosuppression and blood-brain barrier injury could facilitate SARS-CoV-2 entry. Central nervous system SARS-CoV-2 detection should be performed in neurological patients. Abstract: Severe neurological disorders and vascular events during COVID-19 have been described. Here, we describe the first case of a female patient infected with the SARS-CoV-2 BA.2 Omicron variant of concern with meningitis with newly diagnosed central demyelinating disease.